1976
DOI: 10.1071/ea9760911
|View full text |Cite
|
Sign up to set email alerts
|

The role of pycnidiospores of Leptosphaeria maculans in the spread of blackleg disease in rape

Abstract: The development and spread of blackleg leaf, stem and crown infections in rape plants (Brassica napus cv. Zephyr), caused by Leptosphaeria maculans pycnidiospores, was examined under field conditions for plants artificially inoculated at 3, 5 1/2 and 8 1/2 weeks of age. Spread of leaf, stem and crown infections, via pycnidiospores, occurred for inoculations made on 3- and 5 1/2-week-old plants. Inoculation at three weeks oflage resulted in theigreatest disease spread. There was no leaf infection spread and ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 4 publications
1
29
0
1
Order By: Relevance
“…This was in contrast with the observations of Huang et al (2001Huang et al ( , 2003, who reported that germ tubes from A-group ascospores originated predominantly from interstitial cells. In our study, germination from interstitial cells occurred later generating severe epidemics of early seedling disease (Salisbury et al 1995;West et al 2001) and why the epidemics initiated solely by pycnidiospores develop relatively slowly (Barbetti 1976). Inoculum source differences are not expected to affect the results of our study.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This was in contrast with the observations of Huang et al (2001Huang et al ( , 2003, who reported that germ tubes from A-group ascospores originated predominantly from interstitial cells. In our study, germination from interstitial cells occurred later generating severe epidemics of early seedling disease (Salisbury et al 1995;West et al 2001) and why the epidemics initiated solely by pycnidiospores develop relatively slowly (Barbetti 1976). Inoculum source differences are not expected to affect the results of our study.…”
Section: Discussionmentioning
confidence: 93%
“…The biological role of pycnidiospores is to initiate secondary infection cycles following the primary infection by ascospores (Barbetti 1976). Pycnidiospores are splash-borne and are considered to be a less important form of inoculum in some situations (Hall 1992), although they can be a significant inoculum under certain conditions (Barbetti 1976).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Canada have suggested a potential role for conidia as the cause of stem canker symptoms (Barbetti 1976;Guo and Fernando 2005). It was demonstrated by these authors that conidia, even at relatively low concentrations, caused severe disease symptoms on susceptible oilseed rape plants, provided a different cotyledon of the same seedling was co-inoculated with ascospores, suggesting that low concentrations of ascospores might induce susceptibility and increase disease severity in the presence of the sporulating anamorph of the pathogen (Li et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In Australia, the major inoculum of blackleg is ascospores, in combination with pycnidiospores (Barbetti 1976;Marcroft et al 2004). In western Canada, pycnidiospores are the most important sources of inoculum in infection and disease development (Petrie 1995;Guo and Ghanbarnia et al 2011;Dilmaghani et al 2013).…”
Section: Introductionmentioning
confidence: 99%